O ESCRE(VIVER) EM PONCIÁ VICÊNCIO, DE CONCEIÇÃO EVARISTO: Escrita, história e vivência - CAMELO, Luis Fernando Lima (2023)
The present study was the result of an analysis focused on feminist and cultural studies, having as an object of investigation the representation of black women as writers and as a result of the construction of Afro-descendant characters. In this way, the novel Ponciá Vicêncio (2013), by Conceição Evaristo, was used, evidencing deconstructions of the stereotype of black women and their place of speech in society. In addition, the debate on the elements of the ancestry and history of the enslaved people in the novel by Conceição Evaristo. Work that presents identity configurations in the post-slavery period, through the connection between present and past and the representation of the ancestors of the character Ponciá. The theme is justified through the categories of race, gender and class within the Afro-Brazilian literature of female authorship, having as a general objective to analyze the meanings of the notion of writing and the representativeness of the black woman in the constitution of the feminine writing in Ponciá Vicêncio, reflecting the marks of the African diaspora and historical ethnicity, in addition to specifying the female experience, showing cultural and historical particularities of the black woman and as marks of slavery that remain ingrained in Afro-descendants. About the research process, it should be mentioned that it requires mastery in the production of knowledge of theoretical and methodological rigor, based on the analysis of excerpts from Ponciá Vicêncio's work, accepting contributions through Feminist Criticism and Literature by Female Authorship. To support this study, a theoretical survey of some authors who delved into research on the subject was carried out, such as bell hooks (2020), Cuti (2010), Eduardo de Assis (2006), Grada Kilomba (2020), Lélia Gonzalez (2020), Patrícia Hill Collins (2019), among other contemporary researchers who focus on issues related to black feminism, literature and cultural studies. The development of the work allowed us to understand the narrative discourse of Conceição Evaristo, the construction of the black feminine identity in the character Ponciá Vicêncio and the importance of debating the place of speech of the black woman.